THE EFFECT OF INTERNAL AND EXTERNAL FACTORS ON INCOME AND THE SUSTAINABILITY OF GROCERY STORE BUSINESS IN UBUD DISTRICT OF GIANYAR REGENCY, INDONESIA - Mardiana I W.; Marhaeni A.A. I N. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
Competition in traditional markets such as grocery stores with modern stores is currently considered unbalanced, causing the marginalization of small traders. This causes the grocery store to decline more and more. One of the reasons is the rapidly growing minimarket in Bali Province. The growing rapidly of minimarkets will certainly threaten the sustainability of the grocery store business in the vicinity. Based on this, the objectives of this study are 1. To analyze the effect of internal factors and external factors on grocery store revenue; 2. To analyze the effect of internal factors, external factors and income of the grocery store on the sustainability of the grocery store business; 3. To analyze the indirect effect of internal factors and external factors on the sustainability of the grocery store business through the income of the grocery store. This research uses descriptive analysis tools and Structural Equation Model (SEM) with PLS (Partial Least Square). The data used are primary data and secondary data. Data collection used observation methods, structured interviews and in-depth interviews. Respondents in this study were grocery store entrepreneurs in Ubud District, Gianyar Regency, which were taken by quota sampling as many as 120 samples, which were selected by accidental sampling. The result of this research is that the grocery store internal factor variable has a positive and significant effect on the grocery store's income. The grocery store's external factor variable has no effect on the grocery store's income. The variable of the external factor of the grocery store and the variable of the income of the grocery store have a positive and significant effect on the sustainability of the grocery store business. The grocery store internal factor variable has no positive and significant effect on the sustainability of the grocery store business. There is an indirect effect of the grocery store internal factor variable on the sustainability of the grocery store business through the income of the grocery store is significant. There is no indirect effect of the grocery store external factor variable on the sustainability of the grocery store business through the income of the grocery store.